A philosophical interpretation of the unconscious in light of Wilfrid Sellars’ reasons – causes dichotomy - Kuyumcuoğlu Tütüncüoğlu, Nezihe Müge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Wilfrid Sellars’ contribution to the nature versus intellect problem is to challenge the idea that knowledge involves a causal relation between nature and intellect. He transformed the distinction by showing that ontological differences are not relevant as far as knowledge is concerned. Instead, he identified the distinctive feature of the epistemic as normativity in terms of logical-inferential liability, as opposed to the nonepistemic, which is neutral, natural, causal. He epitomized this idea in his distinction of the logical space of reasons versus the material space of causes. I aim to investigate the challenge posed by Sigmund Freud’s psychoanalytic framework of the unconscious to Sellars’ framework, in terms of the space of reasons - space of causes distinction. Specifically, I evaluate Wilfred Bion’s psychoanalytic account of the development of thinking, and apply Sellars’ framework to Bion’s theories. As a result of my analysis, I argue that the logical space of reasons is not limited to conscious endorsements, and that it involves the unconscious as well. This would be possible if we take meaning as an external, inter-subjective reality that the subject has to commit to. Conscious awareness is not required for a subject’s commitment to the meaning of content, propositional awareness is sufficient. If commitment can be differentiated from endorsement, the phenomenon of repression can be logically consistent with this framework.